Optimization of the Cryoprotectants for Direct Vat Set Starters in Sichuan Paocai Using Response Surface Methodology - Lianqun Wu; Zhenying Yang; Ying Zhang; Ling Li; Chunli Tan; Lixia Pan; Yanping Wu; Kai Zhong; Hong Gao (Foods)
The quality of Sichuan paocai in natural fermentation is often inconsistent due to the complexity of its microbial community and environmental influences. To address this, dominant microbial strains were selectively inoculated to improve the product’s quality and safety. However, vacuum freeze-drying, commonly used to prepare direct vat set (DVS) starters, can significantly damage strains due to freezing stress. This study aimed to optimize a freeze-drying protection system for Lactiplantibacillus plantarum and Bacillus subtilis to enhance their survival. Using response surface methodology, combinations of cryoprotectants were evaluated. A formulation comprising skim milk powder, glycerol, sucrose, and L-proline significantly improved strain viability after lyophilization, outperforming single cryoprotectants. Further investigation into storage conditions revealed that low temperatures (−20 °C) provided the best preservation for DVS starters. Furthermore, the optimized DVS starters demonstrated excellent fermentation performance in Sichuan paocai, enhancing its color, flavor, and sensory quality compared to natural fermentation. These findings offer a reliable freeze-drying protection strategy for survival and viability of L. plantarum and B. subtilis.